Construction of a tumor immune infiltration macrophage signature for predicting prognosis and immunotherapy response in liver cancer - Huang, Anmin; Lv, Bei; Zhang, Yunjie; Yang, Junhui; Li, Jie; Li, Chengjun; Yu, Zhijie; Xia, Jinglin (Frontiers in Molecular Biosciences, 2022)
Liver cancer is an extraordinarily heterogeneous malignant disease. The tumor microenvironment (TME) and tumor-associated macrophages (TAMs) are the major drivers of liver cancer initiation and progression. It's critical to have a better understanding of the complicated interactions between liver cancer and the immune system for development of cancer immunotherapy. Based on the gene expression profiles of tumor immune infiltration cells (TIICs), upregulated genes in TAMs and downregulated genes in other type of immune cells were identified as macrophage specific genes (MSG). In this study, we combined MSG, immune subtypes and clinical information of liver cancer to develop a tumor immune infiltration macrophage signature (TIMSig). A four gene signature (S100A9, SLC22A15, TRIM54 and PPARGC1A) was identified as the TAM-related prognostic genes for liver cancer, independent of multiple clinicopathological parameters. Survival analyses shown that patients with low TIMSig had a superior survival rate than those with high TIMSig. Additionally, clinical immunotherapy response and TIMSig was observed as highly relevant. Besides, TIMSig could predict the response to chemotherapy. Collectively, the TIMSig could be a potential tool for risk-stratification, clinical decision-making, treatment planning, and oncology immunotherapeutic drugs development.